Can Asian Models Be Effective to White American Consumers in Values Advocacy Ads? The Implications of Collectivistic Self-Construal as a Self-Motive in the Context of Values Advocacy Ads. Issue 1 (2nd January 2017) - Lee, Yoon-Joo
ABSTRACT: Guided by the motivated reasoning theoretical framework, this study examines the relationship between ethnicity cues (model race) and self-concept (collectivistic self-construal) among white Americans in perceiving values advocacy advertising. The results from experimental studies of 297 general populations, identified as white Americans, suggest that when they have a high level of collectivistic self-construal, they are likely to self-reference to the values advocacy ads featuring Asian models more than to those with white models, resulting in more favorable consumer evaluations (e.g., perceiving advertiser's motives as genuine in advocating social causes). Theoretical and managerial implications are discussed.